The Place-names of Svalbard - Roberts, Brian (Polar Record, 1948)
In the following notes an attempt has been made to summarise the main facts which anyone dealing with the literature and cartography of Svalbard would require to know in order to give a correct rendering of the place-names and to understand the changes in form which have taken place. The writer wishes to express his grateful thanks to Professor A. Sommerfelt for much assistance in connection with the linguistic aspects of the subject, and to Dr Anders K. Orvin, of the Norsk Polarinstitutt, Oslo, who kindly checked the whole manuscript.